Population-based trends and risk factors of early- and late-onset preeclampsia in Taiwan 2001-2014 - Shu-Han You; Po-Jen Cheng; Ting-Ting Chung; Chang-Fu Kuo; Hsien-Ming Wu; Pao-Hsien Chu (BMC, 2018)
Abstract Background Preeclampsia, a multisystem disorder in pregnancies complicates with maternal and fetal morbidity. Early- and late-onset preeclampsia, defined as preeclampsia developed before and after 34 weeks of gestation, respectively. The early-onset disease was less prevalent but associated with poorer outcomes. Moreover, the risk factors between early -and late- onset preeclampsia could be differed owing to the varied pathophysiology. In the study, we evaluated the incidences, trends, and risk factors of early- and late- onset preeclampsia in Taiwan. Methods This retrospective population-based cohort study included all ≧20 weeks singleton pregnancies resulting in live-born babies or stillbirths in Taiwan between January 1, 2001 and December 31, 2014 (n = 2,884,347). The data was collected electronically in Taiwanese Birth Register and National Health Insurance Research Database. The incidences and trends of early- and late-onset preeclampsia were assessed through Joinpoint analysis. Multivariate logistic regression was used to analyze the risk factors of both diseases. Results The age-adjusted overall preeclampsia rate was slightly increased from 1.1%(95%confidence interval [CI], 1.1-1.2) in 2001 to 1.3% (95%CI, 1.2-1.3) in 2012 with average annual percentage change (AAPC) 0.1%/year (95%CI, 0-0.2%). However, the incidence was remarkably increased from 1.3% (95%CI, 1.3-1.4) in 2012 to 1.7% (95%CI, 1.6-1.8) in 2014 with AAPC 1.3%/year (95%CI,0.3-2.5). Over the study period, the incidence trend in late-onset preeclampsia was steadily increasing from 0.7% (95%CI, 0.6-0.7) in 2001 to 0.9% (95%CI, 0.8-0.9) in 2014 with AAPC 0.2%/year (95%CI, 0.2-0.3) but in early-onset preeclampsia was predominantly increase from 0.5% (95%CI, 0.4-0.5) in 2012 to 0.8% (95%CI, 0.8-0.9) in 2014 with AAPC 2.3%/year (95%CI, 0.8-4.0). Advanced maternal age, primiparity, stroke, diabetes mellitus, chronic hypertension, and hyperthyroidism were risk factors of preeclampsia. Comparing early- and late-onset diseases, chronic hypertension (ratio of relative risk [RRR], 1.71; 95%CI, 1.55-1.88) and older age (RRR, 1.41; 95%CI 1.29-1.54) were more strongly associated with early-onset disease, whereas primiparity (RRR 0.71, 95%CI, 0.68-0.75) had stronger association with late-onset preeclampsia. Conclusions The incidences of overall, and early- and late-onset preeclampsia were increasing in Taiwan from 2001 to 2014, predominantly for early-onset disease. Pregnant women with older age and chronic hypertension had significantly higher risk of early-onset preeclampsia.